Cena e presentificação: análise da presença cênica na obra "Maneries", da Cia Luis Garay - Prado, Fernando César (2012)
This is a study of Maneries, a piece from Cia Luis Garay (Buenos Aires-Argentina) starting from the concept of Scenic Presence. We have started by conceptualize Scenic Presenc term as a reality representation starting from the ideia of body training as well as what are understood by the meaning construction of the piece. This study reflects and contextualizes Scenic Presence from Art Thinkers and verticalizes the theme beyond Presence Dispositives as such as the Triple Presence: Construction of Presence, Maitenence of Presence and Virtuality of Presence. Readers follow some interviews with the Cia Luis Garay and their performers where we can have valuable informations about their trajectory as a group of artists. Ending up with conclusion remarks remarks taking into account the main focus of this research.